Development of automatic Landsat data download engine. Issue 1 (December 2020) - Pradono, K A; Safitri, Y D; Adhitama, B S; Hestrio, Y F; Soleh, M; Gunawan, H; Widijatmiko, N; Sunarmodo, W
Abstract: Remote sensing data usually collected by direct acquisition using ground station. But, limitations on acquisition often leads to missing data (especially the old data). United States Geological Survey (USGS), as one of scientific agency and Landsat remote sensing satellite operator, provides access for users to their old to recent remote sensing data. USGS also provides tools to help user to download their data in large or small quantities, but the tools have limitations. The most noticeable limitations are error when downloading and low download speed. At the same time, access and download data in large quantities without tools would takes a lot of time and effort. Hence, an engine to overcome those limitations needs to be developed. By using this engine, users are expected to be able download remote sensing data in large/small quantities automatically, with higher download speed, and less error or corrupt data.